Evaluating The Role of Endometrial Receptivity in IVF Success : A Comprehensive Systematic Review - Made Krisna Wibawa Pramartha; I Made Sudarmayasa (International Medical Journal Corp. Ltd, 2026)
Introduction: Endometrial receptivity is a critical determinant of successful embryo implantation in in vitro fertilization (IVF). Despite advances in assisted reproductive technology, implantation failure remains a significant barrier to successful pregnancy. This systematic review evaluates the role of various endometrial receptivity assessment methods in predicting and improving IVF outcomes. Methods: A comprehensive systematic review was conducted including 80 studies published to 2025. Studies were included if they assessed endometrial receptivity using validated methods (transcriptomic, ultrasound-based, histological, or molecular approaches) and reported IVF outcomes including implantation, clinical pregnancy, or live birth rates. Data were extracted on receptivity measures, IVF success outcomes, cycle types, patient populations, and statistical associations. Results: Endometrial receptivity was assessed using diverse methodologies including transcriptomic testing (ERA, rsERT), ultrasound parameters (thickness, pattern, vascularity, compaction), histological evaluation (pinopodes, chronic endometritis), and molecular biomarkers. Endometrial thickness demonstrated consistent threshold effects: thickness <7-8 mm was associated with significantly lower clinical pregnancy rates (OR 0.42, 95% CI 0.27-0.67) and live birth rates (OR 0.47, 95% CI 0.37-0.61). ERA-guided personalized transfer showed population-dependent efficacy, with significant benefits in recurrent implantation failure (RIF) patients (OR 2.50, 95% CI 1.42-4.40 for clinical pregnancy) but no benefit in good-prognosis populations (RR 0.95, 95% CI 0.79-1.13 for live birth). Chronic endometritis treatment restored normal IVF outcomes, with cured patients achieving comparable pregnancy rates to those without the condition. Endometrial scratching demonstrated variable results, with benefit primarily in RIF patients when performed in the luteal phase (clinical pregnancy RR 2.32, 95% CI 1.72-3.13). Discussion: The clinical utility of endometrial receptivity assessment depends critically on patient selection. In good-prognosis patients with euploid embryos, endometrial factors contribute minimally to success beyond achieving adequate thickness. Conversely, in RIF patients, advanced maternal age, or those with documented endometrial pathology, receptivity assessment and intervention provide meaningful improvements. The interaction between embryo quality and endometrial factors explains substantial heterogeneity in study findings. Conclusion: Endometrial receptivity assessment should be stratified based on patient characteristics. Routine ERA testing in unselected populations is not supported by evidence. Clinical recommendations include: ensuring endometrial thickness ≥8 mm before transfer, screening for chronic endometritis in RIF patients, and considering ERA or endometrial scratching specifically in RIF populations after excluding other causes. Future research should focus on developing integrated assessment approaches combining multiple receptivity parameters.